The Degree to which Principals of Private Schools in Gaza Governorates Practice the Servant Leadership and its Relation to the Quality of their Schools’ Learning - Al-Helo, Ali Omar Darwish (Journal of Educational and Psychological Sciences, 2020)
This study aims at identifying the degree to which principals of private schools in Gaza governorates practice the servant leadership and its relation to the quality of their schools’ learning, the researcher used the descriptive analytical approach. The study population consists of all male and female teachers of the private schools in Gaza governorates, whose number is (1212) teachers. The questionnaire was applied to a sample of (297) male and female teachers. Two questionnaires were designed; the first is to determine degree to which principals of private schools in Gaza governorates practice the servant leadership. It consists of (43) paragraphs divided into three fields. The second is to determine the level of quality of their schools’ learning and consists of (22) paragraphs. The degree to which principals of private schools in Gaza governorates practice the servant leadership from the point of view of the teachers was high, with a relative weight of (75.24%). There were no statistically significant differences at the level of significance (α ≤ 0.05) between the mean scores of the sample estimates to the degree of school principals’ practice to the quality of school learning attributed to the variables (scientific qualification, years of service). There is a direct positive relationship of a statistical significance between the degree of practicing servant leadership and the level of learning quality of their schools.
Keywords: Servant leadership; School principal; Quality of school learning